2018
DOI: 10.1080/19390211.2018.1472709
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Hydroxy-Beta-Methyl-Butyrate, L-glutamine, and L-arginine Supplementation Improves Radiation-Induce Acute Intestinal Toxicity

Abstract: We aimed to evaluate effects of β-hydroxy-β-methylbutyrate, L-glutamine, and L-arginine (HMB/GLN/ARG) on radiation-induced acute intestinal toxicity. Forty rats were divided into four groups: group (G) 1 was defined as control group, and G2 was radiation therapy (RT) control group. G3 and G4 were HMB/GLN/ARG control and RT plus HMB/GLN/ARG groups, respectively. HMB/GLN/ARG started from day of RT and continued until the animals were sacrificed 10 days after RT. The extent of surface epithelium smoothing, villou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…However, the intestinal barrier is easily subjected to hyperthermia due to reduced blood flood to mesenteric circulation, which can negatively affect the integrity of the intestinal epithelium [4]. Accumulating in vitro and in vivo investigations have demonstrated that HS can weaken intestinal integrity and compromise its barrier function [5,6].…”
Section: The Gastrointestinal Systemmentioning
confidence: 99%
“…However, the intestinal barrier is easily subjected to hyperthermia due to reduced blood flood to mesenteric circulation, which can negatively affect the integrity of the intestinal epithelium [4]. Accumulating in vitro and in vivo investigations have demonstrated that HS can weaken intestinal integrity and compromise its barrier function [5,6].…”
Section: The Gastrointestinal Systemmentioning
confidence: 99%
“…The combination of Gln/Arg/HMB may improve recovery through various mechanisms in patients undergoing heart surgery. This compound had beneficial effects on vascular endothelial function [ 31 ], intestinal injuries [ 32 ], pressure ulcers [ 20 , 33 ], immune function [ 34 ], and anastomosis healing [ 35 ]. Moreover, it may prevent muscle wasting [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, ≈300,000 patients receive pelvic radiation per year as part of cancer treatment, and GI radiation‐induced toxicity is 1 of the most reported adverse effects of radiation therapy . In clinical practice, radiation enteritis not only limits the maximum tolerated dose of RT and chemotherapy, sometimes leading to treatment interruptions, but also can cause discomfort for months or even years after treatment is completed . Despite the high prevalence of radiation‐induced intestinal injury, few safe and effective approaches have been successfully used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%